2020
DOI: 10.1177/2277975220965346
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use and Psychosocial Well-being: Role of Mindfulness Mediated by Self-Control and Negative Affect

Abstract: With the growing concern about excessive Internet use and accompanying adverse psychosocial outcomes, unveiling the underlying mechanisms related to problematic Internet use has become an important topic to study. The present study examines the relationship between dispositional mindfulness and psychosocial well-being through problematic Internet use. An attempt has also been made to investigate whether negative affect and self-control are useful in explaining the relationship between dispositional mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
4
0
1
Order By: Relevance
“…Some studies have found that individuals with higher levels of ED are more likely to engage in excessive Internet use as a means of coping with negative emotions and stress; in other words, individuals with ED problems may use the Internet as a form of emotional escape. When they are feeling overwhelmed, anxious, or sad, they may engage in excessive Internet use as a way to distract themselves from their negative emotions and to feel a temporary sense of relief ( Kuss et al, 2017 ; Sinha et al, 2021 ). Relatedly, various unfavorable life events may bring about negative emotions, and the incapacity to manage or regulate these emotions may lead to high levels of impulsivity and the development of dysfunctional behaviors such as excessive Internet use ( Rogier and Velotti, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that individuals with higher levels of ED are more likely to engage in excessive Internet use as a means of coping with negative emotions and stress; in other words, individuals with ED problems may use the Internet as a form of emotional escape. When they are feeling overwhelmed, anxious, or sad, they may engage in excessive Internet use as a way to distract themselves from their negative emotions and to feel a temporary sense of relief ( Kuss et al, 2017 ; Sinha et al, 2021 ). Relatedly, various unfavorable life events may bring about negative emotions, and the incapacity to manage or regulate these emotions may lead to high levels of impulsivity and the development of dysfunctional behaviors such as excessive Internet use ( Rogier and Velotti, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such impulse buying behavior is associated with several adverse consequences, such as financial difficulties ( Fenton-O'Creevy et al, 2018 ) and lower financial well-being ( Nanda and Banerjee, 2021 ). With the savings rate at a record low, financial well-being is found to influence the overall well-being of individuals negatively and has attracted considerable attention in academic research ( Netemeyer et al, 2018 ; Sinha et al, 2021b ) and public policy (e.g., OECD, 2020 ). Many people facing diminished financial well-being create societal problems, leading to adverse welfare effects for today and in the future ( Brüggen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sample items are “It is easy for me to concentrate on what I am doing” and “I am able to pay close attention to one thing for a long period of time”. CAMS—R has been widely used in the field of graduate students, as exemplified by Sinha, who had used the method to measure the mindfulness traits of management graduate students ( Sinha et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%